Current Topics in Salmonella and Salmonellosis - Mares, Mihai (IntechOpen, 2017)
The genus Salmonella comprises an important number of bacterial species able to colonize and infect numerous animal species and humans. Although more than a hundred years passed since its discovery, Salmonella still represents a redoubtable and successful microorganism, difficult to deal with. Whether we discuss about typhoid fever or food poisoning, the public health and financial consequences are practically incalculable. The costs attributable to Salmonella contamination of meat, eggs, and vegetables are also very high worldwide. Antimicrobial resistance in Salmonella isolates is an emerging threat not only in humans, and special measures should be addressed to this global problem. The book Current Topics in Salmonella and Salmonellosis contains a series of reviews about all-important issues concerning these subjects. It comprises 14 chapters grouped in 4 sections emphasizing new insights into pathogenesis, bacterial detection and antibiotic resistance, infections in animals, risk factors, and control strategies. The new genomic data and the exhaustive presentation of molecular pathogenesis bring novelty to the book and can help to improve our knowledge about Salmonella-induced diseases.